Mathematical Study on Alternating Series in a Regular Hexagon–Proof without Words: Exploring a Novel Proof Method for Summation of Alternating Series in a Regular Hexagon (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this paper is to introduce a new approach to prove the sum of an alternating series. This is an approach to prove the sum of an alternating series in a regular hexagon.